'Monetary and fiscal rules in an emerging small open economy' - Batini, Nicoletta (IMF WashingtonUS, 2009)
Develops an optimal rules-based interpretation of the 'three pillars macroeconomic policy framework' and shows how such monetary-fiscal rules need to be adjusted to accommodate specific features of emerging market small open economies.